Bioaccessibility and bioavailability of exogenous and endogenous toxic substances in traditional Chinese medicine and their significance in risk assessment - Tian-Tian Zuo; Jing Liu; Ke Zan; Li-Na Liu; Qi Wang; Zhao Wang; Wei-Yi Xu; Yuan-Xi Liu; Yuan-Sheng Guo; Shuai Kang; Hong-Yu Jin; Feng Wei; et al. (Elsevier, 2024)
Scientific risk assessment of exogenous and endogenous toxic substances in traditional Chinese medicine (TCM) is of great significance. The present review comprises a comprehensive summary of progress in the health risk assessment of harmful exogenous substances in TCMs. Such substances include heavy metals, pesticide residues, biotoxins, and endogenous toxic components involving pyrrolizidine alkaloids. The review also discusses the strengths and weaknesses of various bioaccessibility and bioavailability models, and their applications in risk assessment. Future avenues of risk assessment research are highlighted, including further exploration of risk assessment parameters, innovation of bioaccessibility and bioavailability techniques, enhancement of probabilistic risk assessment combined with bioavailability, improvement of cumulative risk assessment strategies, and formulation of strategies for reducing relative bioavailability (RBA) values in TCMs. Such efforts represent an attempt to develop a risk assessment system that is capable of evaluating the exogenous and endogenous toxic substances in TCMs to ensure its safe use in clinics, and to promote the sustainable development of the TCM industry.